2022
DOI: 10.1098/rsbl.2021.0550
|View full text |Cite
|
Sign up to set email alerts
|

Large and exaggerated sexually selected weapons comprise high proportions of metabolically inexpensive exoskeleton

Abstract: The cost-minimization hypothesis proposes that positive allometry in sexually selected traits can be explained if the proportional energetic maintenance costs of weapons decrease as traits increase in size. Energetic maintenance costs are the costs of maintaining homeostasis. They are slow, persistent energy sinks that are distinct from ephemeral costs of growth. Because some tissues expend more energy on maintenance than others, energetic maintenance costs can be inferred from proportional tissue composition.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Larger weapons produce longer-lasting cavitation bubbles and greater pressures ( Dinh and Patek, 2023 ). However, individuals that grow larger weapons than predicted by snapping claw scaling relationships do so using less muscle and more exoskeleton ( Dinh, 2022 ). Reducing the amount of muscle in the claw may hinder elastic loading and snap production.…”
Section: Resultsmentioning
confidence: 99%
“…Larger weapons produce longer-lasting cavitation bubbles and greater pressures ( Dinh and Patek, 2023 ). However, individuals that grow larger weapons than predicted by snapping claw scaling relationships do so using less muscle and more exoskeleton ( Dinh, 2022 ). Reducing the amount of muscle in the claw may hinder elastic loading and snap production.…”
Section: Resultsmentioning
confidence: 99%
“…Arrows represent behavioural transitions that occur more often than predicted if transitions were random, and arrow width represents transitional probabilities. with positive allometry (Dinh, 2022). Previous work has suggested that snapping shrimp shield their body from incoming snaps using their snapping claw, so positive allometry of claw exoskeleton could reflect scaling of defensive capacity (Herberholz & Schmitz, 1998).…”
Section: Discussionmentioning
confidence: 98%
“…Large mantis shrimp have thicker telsons, dissipate more energy and can withstand greater forces than small mantis shrimp (Taylor & Patek, 2010). In snapping shrimp, the exoskeleton of the weapon scales with positive allometry (Dinh, 2022). Previous work has suggested that snapping shrimp shield their body from incoming snaps using their snapping claw, so positive allometry of claw exoskeleton could reflect scaling of defensive capacity (Herberholz & Schmitz, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of the claw made of muscle decreases as weapon residual increases (Dinh, 2022). Therefore, we tested whether weapon residuals were negatively correlated with average angular velocity in the snapping claw, cavitation bubble duration, and snap pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Larger weapons produce longer-lasting cavitation bubbles and greater pressures (Dinh & Patek, 2022). However, individuals that grow larger weapons than predicted by snapping claw scaling relationships do so using less muscle and more exoskeleton (Dinh, 2022). Reducing the amount of muscle in the claw may hinder elastic loading and snap production.…”
Section: Introductionmentioning
confidence: 99%